From Cell to Symptoms: The Role of SARS-CoV-2 Cytopathic Effects in the Pathogenesis of COVID-19 and Long COVID (2023)
Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) infection triggers var-ious events from the molecular to the tissue level, which in turn is given by the intrinsic character-istics of each patient. Given the molecular diversity characteristic of each cellular phenotype, the possible cytopathic, tissue, and clinical effects are difficult to predict, which determines the hetero-geneity of COVID-19 symptoms. The purpose of this article is to provide a comprehensive review of the cytopathic effects of SARS-CoV-2 on various cell types, focusing on the development of COVID-19, which in turn may lead, in some patients, to the persistence of symptoms after recovery from the disease, a condition known as long COVID. We describe the molecular mechanisms un-derlying virus–host interactions, including alterations in protein expression, intracellular signaling pathways, and immune responses. In particular, the article highlights the potential impact of these cytopathies on cellular function and clinical outcomes, such as immune dysregulation, neuropsy-chiatric disorders, and organ damage. The article concludes by discussing future directions for re-search and implications for the management and treatment of COVID-19 and long COVID.